Pelatihan Mixology kepada Siswa SMK Al-Azhar Batam - Sipayung, Natal Olotua; Dailami; Moh. Thandzir; Rais, Syafruddin Rais; saputra, Ardiansyah Saputra (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
Mixology is the art of creating a drink that is good in taste and appearance. In making this drink, there are several methods, they are pouring, shaking, blending, layering, and stirring. In making this drink you also need several equipment such as a jigger, shaker, blender, long bar spoon, knife, cutting board and tong.. The drink container (glass) also influences the appearance of the drink. For mocktail drinks, the following glasses are usually used as containers, they are highball glass, hurricane glass, pocogrande glass, and cocktail glass. The mixology training activity for AL-Azhar Vocational School students was carried out in the AL-Azhar Vocational School field, the presenter first gave an explanation, practiced how to make drinks, then gave several students the opportunity to make drinks and finally the students drank the mocktails that had been prepared by the presenter.